Analisis Pelanggaran Etika Periklanan (EPI) Iklan TV : Studi Kasus Pada Iklan Ichitan Versi Mau Yang Asli - Wardatul Jannah; Intan Sari; Rosita Tri Cahya (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This study analyzes ethical violations in advertising (EPI) within television commercials, using the Ichitan "Want the Real One" commercial as a case study. The primary objective of this research is to identify and disseminate the ethical breaches occurring in the advertisement and their impact on consumer perception. The research method employed is qualitative content analysis with a descriptive approach. Data were collected through advertisement observation and a literature review related to advertising ethics. The study results indicate that the Ichitan "Want the Real One" commercial violates several principles of advertising ethics, including the use of misleading claims and inaccurate representations. The impact of these violations is the emergence of negative perceptions among consumers toward the Ichitan brand. This research suggests that advertisers should adhere more closely to ethical standards in creating advertisements to maintain consumer trust and reputation.